Antioxidant and Antibacterial Activities of Terminalia superba Engl. and Diels (Combretaceae) Bark Extracts - Kougnimon, Fifamè Espérance Elvire; AKPOVI, DEWANOU CASIMIR; Dah-Nouvlessounon, Durand; LOKO, CHRISTIAN FRÉDÉRIC SIMPLICE (My University, 2018)
Terminalia superba (T. superba) is locally used for the treatment of various diseases, including diabetes mellitus, gastroenteritis, female infertility, abdominal pains, bacterial, fungal and viral infections. This study aimed to ascertain the antioxidant and antimicrobial activities of ethanolic and hydro-ethanolic extracts of T. superba barks. Total phenols, flavonoids, and tannins were measured in the extracts by a spectrophotometry method. The DPPH method was used to evaluate extracts antioxidant activity. The antibacterial activity was evaluated using broth micro-dilution method in vitro on Staphylococcus aureus isolated clinical strains from three skin infections (buruli ulcer, furuncles and abscesses) and a Staphylococcus aureus reference strains (Staphylococcus aureus ATCC 29213). Clinical strains were multi drug resistant with or without a virulence factor (Panton-Valentine Leukocidin (PVL).The phytochemical screening of ethanolic and hydro-ethanolic extracts of T. Superba barks revealed the presence of tannins (catechic and gallic), flavonoids, saponins, free anthracene derivatives, reducing compounds, mucilage. Ethanolic and hydro-ethanolic extracts showed antioxidant activities. Both extracts had antibacterial activities on Staphylococcus aureus ATCC 29213 and S. aureus isolated from skin infections. This study shows that T. superba has high antibacterial and antioxidant activities
Keywords: Terminalia superba; Bark; antibacterial activity; antioxydant activity